Implementation of MASS Drug Prevention Program Grant (POMP) Filariasis in Pekalongan (Universitas Negeri Semarang, 2018)
Coverage of Pekalongan City filariasis medicine after the implementation of the five-year program POMP Filariasis is still less than 65% and the Mf rate is still 1% so that it is still declared as a filariasis endemic area. This study aims to analyze the factors that influence the implementation of the Filariasis MDA program held in Pekalongan City. This research is a type of qualitative research by analyzing the content or discussion content. Determination of informants using the snowball sampling technique. The results of this study indicate that the Input component: Infrastructure facilities in the POMP prorogram have been provided by the Health Office but are still not adequate; Human resources, especially from health workers, are still lacking, funding is still Considered inadequate. Process Component: Implementation of socialization is still not optimal because of the lack of budget funds for socialization; Output component: Low public knowledge about the program has an impact on the lack of compliance with medication and lack of public awareness to live clean and healthy lives. Pekalongan City Health Center is expected to increase of socialization to the community regarding Filariasis MDA programs through various types of media, such as television, radio, and banner installation.